2010
DOI: 10.1161/hypertensionaha.109.140061
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Receptor Agonistic Autoantibody Is Highly Prevalent in Preeclampsia

Abstract: Abstract-Preeclampsia (PE), a syndrome affecting 5% of pregnancies, characterized by hypertension and proteinuria, is a leading cause of maternal and fetal morbidity and mortality. The condition is often accompanied by the presence of a circulating maternal autoantibody, the angiotensin II type I receptor agonistic autoantibody (AT 1 -AA). However, the prevalence of AT 1 -AA in PE remains unknown, and the correlation of AT 1 -AA titers with the severity of the disease remains undetermined. We used a sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 24 publications
5
111
0
4
Order By: Relevance
“…Clinical data have confirmed that severe PE in patients is associated with higher circulating AT 1 -AA and sFlt-1 levels, demonstrating a link between these mediators and pathogenesis of the disease (59,60). This study is the first to measure changes in the production of AT 1 -AA and sFlt-1 in response to VD supplementation.…”
Section: R350 Vit D Improves Pathophysiology In Preeclamptic Rat Modelmentioning
confidence: 54%
“…Clinical data have confirmed that severe PE in patients is associated with higher circulating AT 1 -AA and sFlt-1 levels, demonstrating a link between these mediators and pathogenesis of the disease (59,60). This study is the first to measure changes in the production of AT 1 -AA and sFlt-1 in response to VD supplementation.…”
Section: R350 Vit D Improves Pathophysiology In Preeclamptic Rat Modelmentioning
confidence: 54%
“…Furthermore, AT1-AA stimulates sFlt-1 and sEng by inducing TNF-a and overcoming its negative regulator, HO (59). In terms of human studies, Stepan et al (60) did not find a correlation between AT1-AA and sFlt-1 levels, whereas Siddiqui et al (61) did. Given these mixed results in humans, it remains questionable whether AT1-AA and sFlt-1 levels share the same pathophysiologic mechanism.…”
Section: Angiotensin Receptor 1 Autoantibodiesmentioning
confidence: 99%
“…Another 10 blood experimental biomarkers (AT-1AA [31], calcyclin, copeptin [34], galectin-1 [36], Gas6 [37], HIF-1aOH [38], IGFALS [41], mammalian HtrA3 [45], NT-proBNP [47], and PTX3 [49]), and four urine ones (C5b-9 [33], nephrin [46], iodine [42], and prolactin [52]) had limited clinical evaluation information, which impeded the evaluation of their performance for the diagnosis of PE. No clinical data were found for the remaining nine blood markers, which consisted of adipsin, α enolase, ADMA, Ba, 2,3-BPGM, Fetal DNA, marinobufagenin, plasma UA [51], and soluble CD117.…”
Section: Resultsmentioning
confidence: 99%